1997
DOI: 10.3354/ame012251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazer and substrate amendments on nutrient and plankton dynamics in estuarine enclosures

Abstract: ABSTRACT. We compared the effects of substrate C:N ratio and macrozooplankton activity on nutrient and chlorophyll dynamics by amending the substrate C:N ratios in carboys contain~ng natural estuarine microplankton [<200 pm) with additions of glucose (High C:N), arginine (Low C:N), or nothing (Control). Adult copepods (Acartla tonsa, 10 ind. 1.' ) were added to 1 carboy of each substrate treatment. Water and copepods were collected from the Choptank River, a subestuary of the Chesapeake Bay (USA) in August 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Aureococcus anophagefferens can grow efficiently on urea in culture (Dzurica et al 1989), and it has been reported that most of the N assimilated by blooms is from urea (Berg et al 1997). However, the failure of urea additions to increase the relative abundance of A. anophagefferens among phytoplankton in 9 of 10 experiments (Figs.…”
Section: Nitrogenmentioning
confidence: 81%
See 3 more Smart Citations
“…Aureococcus anophagefferens can grow efficiently on urea in culture (Dzurica et al 1989), and it has been reported that most of the N assimilated by blooms is from urea (Berg et al 1997). However, the failure of urea additions to increase the relative abundance of A. anophagefferens among phytoplankton in 9 of 10 experiments (Figs.…”
Section: Nitrogenmentioning
confidence: 81%
“…It has been proposed that inorganic N inputs can repress the formation of brown tides (Keller & Rice 1989, LaRoche et al 1997, while organic N inputs stimulate them (LaRoche et al 1997), and that urea is the organic N compound most important for sustaining Aureococcus anophagefferens blooms (Berg et al 1997). The decrease in relative abundance of A. anophagefferens among phytoplankton in our N-addition treatments when ambient nitrate levels were relatively high (average > 7 µM; 31 May, 4, 8, 12, 22 June) supports the hypothesis that eutrophic conditions (>10 µM labile N) do not favor the initiation of monospecific brown tides (Keller & Rice 1989, Nixon et al 1994, LaRoche et al 1997).…”
Section: Nitrogenmentioning
confidence: 99%
See 2 more Smart Citations
“…As the cells degraded, the release of organic matter presumably stimulated microbial activity, as has been observed following the addition of glucose or arginine during phytoplankton growth and decay experiments with Chesapeake Bay waters (Miller et al 1997 (Stumm and Morgan 1996). In studies in which fulvic acid was added to inorganic particles, creation of an organic coating enhanced Hg(II) sorption (Xu and Allard 1991;Gagnon and Fisher 1997).…”
Section: Discussionmentioning
confidence: 99%